A Block Diagram of Electromagnetoelastic Actuator Nanodisplacement for Communications Systems - Afonin, S. M. (Discoveries in Agriculture and Food Sciences, 2018)
The parametric block diagram of the electromagnetoelastic actuator nanodisplacement or the piezoactuator is determined in contrast the electrical equivalent circuit types Cady or Mason for the calculation of the piezoelectric transmitter and receiver, the vibration piezomotor with the mechanical parameters in form the velosity and the pressure. The method of mathematical physics is used. The parametric block diagram of electromagnetoelastic actuator is obtained with the mechanical parameters the displacement and the force. The transfer functions of the electroelastic actuator are determined. The the generalized parametric block diagram, the generalized matrix equation for the electromagnetoelastic actuator nanodisplacement are obtained. The deformations of the electroelastic actuator for the nanotechnology are described by the matrix equation. Block diagram and structural-parametric model of electromagnetoelastic actuator nanodisplacement for nanodisplacement of the communications systems are obtained, its transfer functions are bult. Effects of geometric and physical parameters of electromagnetoelastic actuators and external load on its dynamic characteristics are determined. For calculations the communications systems with the piezoactuator for nanodisplacement the parametric block diagram and the transfer functions of the piezoactuator are obtained.